Principal diseases of marine fish and shellfish - Sindermann, Carl J. (Academic Press, 1990)
This Second Edition has been expanded to two volumes, the first of which focuses on marine fish. Volume 1 reviews the important diseases of wild, captive, or cultivated fish species, fish immunology, the effects of disease on populations, and public health aspects of fish diseases. Fishery scientists and managers, marine biologists, marine ecologists, and marine aquaculturists will find this volume indispensable.